Method for preparing solvent-soluble component through lignite ozone oxidation depolymerization

The oxidation and depolymerization of lignite macromolecules under mild conditions by ozone oxidation method solves the problems of low oxidation efficiency and difficulty in separation in the prior art, realizes efficient and low-cost preparation and separation of solvent-soluble components, and provides coal New ways to use cleanliness.

CN119193195APending Publication Date: 2024-12-27CHINA UNIV OF MINING & TECH

Patent Information

Application Number
CN202411594637.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lignite oxidation preparation solvent soluble component technology has problems such as low oxidation efficiency, high oxidant cost, difficult oxidation degree, and difficulty in separation of oxidation products, which leads to the inability to be widely used in industry.

Method used

By using the ozone oxidation method, by stirring the mixture of lignite with ozone and oxygen in acetic acid or water at room temperature, the ozone yield and oxidation time are controlled to achieve oxidative depolymerization of macromolecules, and solvent-soluble components are generated, and filtration is carried out by centrifugation. Realize direct separation of products.

Benefits of technology

It has achieved efficient conversion of lignite macromolecules with high yield of solvent soluble substances, strong oxidation activity, low cost, and no oxidant components in the product, simplifying the separation process and providing a new method for clean and efficient utilization of coal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193195A_ABST
    Figure CN119193195A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a solvent soluble component through lignite ozone oxidation depolymerization, and belongs to the technical field of lignite deep processing. The method comprises the following steps: weighing lignite, adding the lignite into acetic acid or water, introducing a mixed gas of ozone and oxygen into a system, and carrying out a stirring reaction at room temperature; and after the reaction is finished, centrifugally filtering the mixture, and collecting a liquid sample. According to the method, the solvent-soluble component is prepared through depolymerization of ozone oxidation lignite, the ozone production cost is low, the oxidation activity is high, accurate regulation and control of the oxidation depolymerization depth of lignite macromolecules can be achieved under the mild condition, the lignite macromolecules are promoted to be directionally converted into the solvent-soluble component under the mild condition, the yield of solvent-soluble substances is high, and the method is suitable for industrial production. And a new thought is provided for clean and efficient utilization of coal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lignite deep processing, and in particular to a method for preparing solvent-soluble components by ozone oxidation and depolymerization of lignite. Background Art

[0002] The reserves of lignite in my country are abundant and concentrated. The proven reserves of lignite are about 131.142 billion tons, accounting for 17% of the total reserves of domestic coal resources. Its biggest characteristics are high moisture, low calorific value and high volatile matter, which lead to low direct combustion efficiency and waste of resources. Oxidative depolymerization is one of the most important means of deep processing and utilization of lignite. In addition to rich lignite wax and humic acid, lignite also retains a relatively complete macromolecular structure of coal-forming plants and contains a large number of oxygen-containing functional groups, such as carboxyl, ketone, carbonyl, aldehyde and oxygen-containing bridge bonds. In particular, the ether bridge bond content is high and the bond energy is low. Solvent-soluble components can be obtained by oxidative depolymerization of macromolecular clusters and insoluble organic macromolecular network skeleton structures in lignite. However, in the current existing technology for preparing solvent-soluble components by oxidation of lignite, there are mainly problems such as low yield of solvent-soluble components and difficulty in separating and purifying the products generated after oxidative depolymerization.

[0003] According to the different oxidation methods, the oxidation of lignite can be divided into O 2 / alkali oxidation, ruthenium ion catalytic oxidation, hydrogen peroxide oxidation, sodium hypochlorite aqueous solution oxidation and peroxy organic acid oxidation. 2 The oxidation activity is low, and it is difficult to effectively oxidize and depolymerize lignite under mild conditions. 2 / Alkali oxidation of lignite will introduce a large amount of alkali into the product, making it difficult to separate the subsequent products and requiring a high reactor; ruthenium ion catalytic oxidation activity is high, but the catalyst is relatively expensive, and the cost is too high, which will also cause the presence of ruthenium ions in the product, making it difficult to separate; hydrogen peroxide oxidation also has certain disadvantages, its chemical properties are unstable, and its own decomposition rate will accelerate with the increase of temperature, which is not conducive to the oxidation and depolymerization of lignite; sodium hypochlorite aqueous solution oxidation effect is better, but it is difficult to control the oxidation depth, often resulting in excessive oxidation of oxidation intermediates to carbon dioxide, and organic compounds containing chlorine elements will be generated in the product, further increasing the difficulty of subsequent separation and purification; and peracetic acid is a highly active oxidant, but it is very unstable during storage and use. Therefore, the current oxidation technology still has problems such as low oxidation efficiency, expensive oxidant cost, difficult to control oxidation degree, difficult to separate oxidation products, and unstable oxidant, which makes it impossible to be applied on a large scale in actual industrial production. The development of efficient, controllable, simple oxidation technology and easy to achieve product separation is of great significance for the oxidation and depolymerization of lignite to generate solvent-soluble components. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite, which is simple, efficient and easy to separate products.

[0005] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite, comprising the following steps:

[0006] Weigh lignite, add acetic acid or water, introduce a mixed gas of ozone and oxygen into the system, and stir to react at room temperature; after the reaction is completed, centrifuge and filter the mixture to collect a liquid sample.

[0007] Preferably, the stirring speed is 300-500 rpm, and the stirring time is 1.5-6 h.

[0008] Preferably, the lignite is selected from one of Shengli lignite (SL), Naomaohu coal (NMH), Xiaolongtan coal (XLT), Shendong pulverized coal (SDP), Shendong lump coal (SDC) and Mengdong coal (MD).

[0009] Preferably, the solid-to-liquid ratio of the lignite to acetic acid or the lignite to water is 1-4:30 g / mL.

[0010] Preferably, the ozone is generated by the following steps: introducing high-purity oxygen into the ozone generator, adjusting the oxygen flow rate to 0.5 L / min, and the ozone output to 20-40 m 3 / h, the mixed gas of ozone and oxygen passes through the ozone detector and then directly into the acetic acid or water system.

[0011] Furthermore, the solid residue obtained by centrifugal filtration is directly added to acetic acid or water for further oxidative depolymerization.

[0012] Ozone is a highly oxidizing agent and a nonlinear triatomic molecule with an obtuse bond angle and two equidistant oxygen-oxygen bonds. Compared with traditional oxidants (oxygen, hydrogen peroxide, nitric acid, etc.), ozone has the advantages of high oxidative activity, mild and controllable oxidation conditions, fast reaction speed, and mature production technology. It can achieve precise control of the depth of oxidative depolymerization of lignite macromolecules under mild conditions, and promote the directional conversion of lignite macromolecules into solvent-soluble components under mild conditions. In addition, ozone can react with carbon-carbon double bonds to destroy aromatic ring structures or fatty bonds. Ozone will undergo electrophilic oxidation with coal tar. Ozone molecules will attack carbon atoms on aromatic rings to generate hydroxyl or carbonyl groups, thereby producing a large number of oxygen-containing aromatic compounds. Ozone oxidation can destroy the covalent bonds in the macromolecular structure of coal, effectively depolymerize the macromolecular structure in coal, and promote the formation of weak bonds during the liquefaction process. In addition, the depth of ozone oxidation can be controlled by controlling the ozone output and oxidation time, inhibiting the deep oxidation of lignite into small molecular compounds, thereby controlling the conversion of most of the lignite organic matter into solvent-soluble components.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] 1. The present invention can effectively crack the macromolecular structure in lignite and mainly convert it into solvent-soluble components by conducting ozone oxidation depolymerization experiments on different lignites including Shengli lignite (SL), Naomaohu coal (NMH), Xiaolongtan coal (XLT), Shendong pulverized coal (SDP), Shendong lump coal (SDC) and Mengdong coal (MD). The organic matter conversion rate of all lignites after one oxidation is more than 55%, and the mass of the solid product obtained by evaporating the liquid after oxidative depolymerization is more than 0.32g. In the fifth cycle oxidation process of SL, the organic matter conversion rate reached 81.15%, the total evaporated liquid mass was 1.7816g, and the total macromolecular product yield was 60.18%; in the third cycle oxidation process of NMH, the organic matter conversion rate reached 91.17%, the total evaporated liquid mass was 3.1130g, and the total macromolecular product yield was 83.77%. Therefore, after cyclic oxidation, the solvent soluble yield obtained for SL was greater than 60.18%; and the solvent soluble yield obtained for NMH was greater than 83.77%.

[0015] 2. The present invention prepares solvent-soluble components through ozone oxidation and depolymerization of lignite. The ozone production cost is low and the oxidation activity is high. Under mild conditions, the depth of oxidative depolymerization of lignite macromolecules can be precisely regulated, thereby promoting the directional conversion of lignite macromolecules into solvent-soluble components under mild conditions. The yield of solvent-soluble substances is high, and the reaction products are directly filtered and separated without containing oxidant components, which provides a new idea for the clean and efficient utilization of coal. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the liquid product of SL oxidation by ozone;

[0017] Figure 2 is the time gradient diagram of ozone oxidation SL;

[0018] Figure 3 is the ozone production gradient diagram of ozone oxidation SL;

[0019] Figure 4 (a) Liquid and (b) Liquid-to-Dry Solid Graphs of Different Lignite Ozone Oxidation;

[0020] Figure 5 is the graph of conversion rate and liquid evaporated solid mass of different lignite ozonation;

[0021] Figure 6 are the liquid diagrams of the secondary oxidation of the residues of the primary ozone oxidation of (a) SL and (b) NMH;

[0022] Figure 7Schematic diagram of the cycle experiment of ozone oxidation of (a, c) SL and (b, d) NMH;

[0023] Figure 8 are the XRD patterns of different lignites and remaining residues;

[0024] Fig. 9 are the GPC graphs of (a) SL and (b) NMH ozone-oxidized liquid evaporated solids;

[0025] Fig.10 (a, c) SL and (b, d) NMH ozone oxidation liquid evaporated solid liquid NMR hydrogen and carbon spectra;

[0026] Fig.11 (ac) XPS C 1s of the liquid-dried solids oxidized by ozonation of SL and (df) NMH; (gi) XPS O 1s of the liquid-dried solids oxidized by ozonation of SL and (jl) NMH;

[0027] Fig.12 are SEM images of different samples. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0029] The lignite samples used in the following examples include Shengli lignite (SL), Naomaohu coal (NMH), Xiaolongtan coal (XLT), Shendong pulverized coal (SDP), Shendong lump coal (SDC) and Mengdong coal (MD), which are ground to less than 40 mesh and directly used in oxidation experiments without any treatment.

[0030] The English abbreviations used in the following examples and their explanations are as follows: ORA: Oxidized residue acetic acid, ORW: Oxidized residue water, OLA: Oxidized liquid acetic acid, OWA: Oxidized liquid water, C: Cycle, D: Dry.

[0031] Examples 1-25

[0032] Weigh 1g or 4g of lignite into a three-necked flask, add 30mL of acetic acid or deionized water, and connect the device. Open the oxygen cylinder and adjust the oxygen flow rate entering the ozone generator to 0.5L / min. The ozone production is 0, 20, and 40m3 respectively. 3 / h, the mixed gas of ozone and oxygen is directly introduced into a three-necked flask after passing through an ozone detector. At room temperature (30°C), a magnetic stirrer is used for stirring at a speed of 300-500rpm, and the stirring is maintained for a certain period of time. The lignite and ozone undergo oxidation reaction in the atmosphere of acetic acid or deionized water. After the reaction is completed, the mixture is centrifuged and filtered, the color of the liquid sample is photographed and recorded, the solid residue is washed twice with acetic acid or deionized water, and dried at 105°C overnight for weighing, all the liquid samples after filtration are dried at 105°C overnight, and the solid samples after evaporation are collected and weighed. For the cyclic experiment, the solid residue after each use is directly used for the next round of oxidation experiment. The detailed reaction conditions and related product numbers of ozone oxidation of different lignites are shown in Table 1. The calculation process of conversion rate and yield is as follows:

[0033] m 3 =mm 1 -m×M ad (g) Formula 1

[0034]

[0035] In the above formula, m: lignite mass, g;

[0036] m 0 : Total evaporated liquid mass, g;

[0037] m 1 : Remaining residue mass, g;

[0038] m 2 : mass of organic matter converted in one pass, g;

[0039] m 3 : Total transformed organic matter mass, g;

[0040] m 4 : Mass of liquid evaporated in one pass, g.

[0041] Table 1 Reaction conditions and related product numbers of ozone oxidation of different lignites

[0042]

[0043] The liquid products of SL under different ozone oxidation conditions are shown in the figure Figure 1 As shown. Figure 1 (a) It can be seen that when acetic acid is used as the solvent, as the oxidation time increases, the color of the liquid product gradually deepens from yellow to brown. Figure 1 (b) It can be seen that when deionized water is used as the solvent, as the oxidation time increases, the color of the liquid product gradually deepens. Figure 1(c) It can be seen that when acetic acid is used as the solvent, as the ozone production during the oxidation process increases, the color of the liquid product can be observed to gradually deepen.

[0044] Depend on Figure 2 It can be seen that when acetic acid is used as the solvent, the organic matter conversion rate of lignite gradually increases with the increase of oxidation time, from 31.36% at 1.5h to 60.51%; when deionized water is used as the solvent, the organic matter conversion rate of lignite also shows a gradual increasing trend with the increase of oxidation time, from 3.13% at 1.5h to 34.23%. The results show that compared with deionized water, under the same conditions, the effect of ozone oxidation depolymerization of lignite is better when acetic acid is used as the solvent, and the lignite organic matter conversion rate is higher.

[0045] Depend on Figure 3 It can be seen that when acetic acid is used as the solvent and the ozone production is 0 (i.e., Example 5), that is, only oxygen is introduced into the device, the degree of oxidative depolymerization of lignite is low, and the organic matter conversion rate obtained is 3.23%. With the increase of ozone production, the organic matter conversion rate of lignite increases rapidly. When the ozone production is 20m 3 / h, it reached 50.64%, and the ozone production was 40m 3 / h, it reached 58.92%.

[0046] Comparison of Examples 6, 17, 22-25 was conducted to explore the ozone oxidation depolymerization experimental results of different lignites including SL, NMH, XLT, SDP, SDC and MD. Figure 4 As shown, the liquids oxidized by ozone of different lignites are mainly light yellow and light brown, and the solid products of the corresponding liquids evaporated to dryness are mainly dark brown, which is the typical color of humic acid.

[0047] Depend on Figure 5 As far as we know, among the lignite samples studied, NMH and SDP have the highest organic matter conversion rates, reaching 75.41% and 77.10% respectively in only one oxidation process, and the mass of the solid products obtained after oxidative depolymerization of the two liquids is the highest, reaching 0.4886g and 0.4935g respectively. In general, the organic matter conversion rate of all lignites reached more than 55%, and the mass of the solid products obtained after oxidative depolymerization liquids was more than 0.32g. The corresponding results show that lignite can be mainly converted into solvent-soluble large molecular weight components through ozone oxidative depolymerization, and the obtained liquid evaporation solid products can be dissolved in solvents such as methanol, ethanol, tetrahydrofuran, acetic acid and water. The ozone oxidative depolymerization experiment was carried out at room temperature (30°C), and for the acetic acid solvent used, the solvent recovery rate can be guaranteed to be above 98.5%.

[0048] The solid residue remaining after the primary conversion of SL and NMH is further oxidized to obtain a liquid such as Figure 6 As shown in Figure 2, it can be observed that the liquid color becomes relatively lighter, but the organic matter conversion rate increases from 58.92% to 86.65% and from 75.41% to 85.57%, respectively. The results show that secondary oxidation can further improve the conversion of organic matter in lignite into solvent-soluble components.

[0049] Taking SL and NMH as examples, the amount of lignite input was increased from 1g to 4g, and multiple cycles of oxidative depolymerization of SL and NMH were conducted. Figure 7 It can be seen that the color of the SL liquid becomes lighter after 5 cycles, while the color of the NMH liquid becomes lighter after only 3 cycles.

[0050] As shown in Table 2, the total organic matter conversion rate of SL and NMH gradually increased with the increase of the number of cycles in the ozone oxidation depolymerization experiment at room temperature (30°C). SL reached 81.15% at the 5th time, and NMH reached 91.17% at the 3rd time. After 5 cycles of oxidation experiments, the total evaporated liquid mass of SL was 1.7816g, and the total macromolecular product yield was 60.18%; after 3 cycles of oxidation experiments, the total evaporated liquid mass of NMH was 3.1130g, and the total macromolecular product yield was 83.77%. Since the small molecular solvent-soluble components with lower boiling points will be evaporated during the liquid evaporation process, the ozone oxidation depolymerization experiment at room temperature (30°C) has a solvent-soluble yield of more than 60.18% for SL; and more than 83.77% for NMH.

[0051] Table 2 Cycle test results of ozone oxidation of SL and NMH

[0052]

[0053] Elemental analysis was performed on different lignites, oxidation residues and corresponding liquid evaporated solid products, and the results are listed in Table 3. As can be seen from Table 3, after oxidative depolymerization of different lignites, the oxygen content in the remaining solid residues and liquid evaporated solid products increased relative to the original coal. For SL and NMH, as the number of cycles of oxidative depolymerization increased, the oxygen content in the remaining solid residues and liquid evaporated solid products gradually increased, and the O / C ratio also gradually increased. The results show that the ozone oxidative depolymerization process will cause oxygen atoms to gradually enter the product, and the product contains relatively more oxygen-containing functional groups.

[0054] Table 3 Elemental analysis results of different samples

[0055]

[0056]

[0057] Industrial analysis of different lignites and oxidation residues is performed, and the results are listed in Table 4. As can be seen from Table 4, there is a lot of ash in SL, SDP and MD samples. For SL and NMH, after oxidative depolymerization, the ash content in the residue gradually increases and the fixed carbon content gradually decreases. The results show that the ozone oxidation process mainly decomposes the organic matter in the lignite, and the ash remains in the solid residue.

[0058] Table 4 Industrial analysis results of different samples

[0059]

[0060] like Figure 8 As shown in the XRD spectrum, different lignites and oxidation residues show different characteristic peaks. For SL, SDP, XLT and the corresponding oxidation residues, an obvious characteristic diffraction peak can be observed at a 2θ value of about 27°, which is attributed to SiO 2 , which is the main component of ash in coal samples; while for NMH, almost no corresponding diffraction peaks were observed. From the industrial analysis results of coal samples, it can be seen that the main reason is that SL and SDP have higher ash contents, followed by XLT and finally NMH. Therefore, the SiO 2 The diffraction peak intensity of XLT SiO 2 The diffraction peak intensity of NMH is relatively weak, and the lower ash content in NMH makes SiO 2 The diffraction peak intensity of SiO 2 The coal sample with the diffraction peak still appears in the remaining residue after oxidation, indicating that SiO 2 It is not dissolved and still exists in the remaining residue.

[0061] The molecular weight of the evaporated solids of SL and NMH ozone oxidized liquids was determined by GPC. Fig. 9 As shown, the molecular weights of all samples are mainly concentrated in the range of 250-500Da. According to the molecular weight distribution results, it can be seen that the solvent-soluble components obtained are mainly similar to fulvic acid in humic acid, which basically have the same molecular weight distribution.

[0062] Liquid NMR hydrogen spectrum and carbon spectrum test were performed on SL and NMH ozone oxidation liquid evaporated solid. Fig.10It can be seen that the liquid NMR hydrogen spectrum and carbon spectrum of the SL ozone-oxidized liquid evaporated solid are basically the same as the NMH results. There are CC bonds, C=C bonds, COC bonds, and a large number of oxygen-containing hydroxyl and carboxyl groups in the structure. Since the hydrogen signal detected connected to the benzene ring is weak, it is inferred that the benzene ring is mainly distributed with substituted hydroxyl and carboxyl groups, which is consistent with the structure of humic acid, especially fulvic acid. The corresponding results also show that ozone can effectively crack the macromolecular structure in lignite into solvent-soluble components, and the product contains relatively more oxygen-containing groups, such as hydroxyl and carboxyl groups.

[0063] XPS was performed on the liquid evaporated solids from the SL and NMH ozone oxidation cycle experiments to observe the different chemical valence states of C and O in the samples. Fig.11 As shown in the figure, for the liquid evaporated solids of the two SL and NMH ozone oxidation cycle experiments, with the increase of the number of cycles, the C1s graph of XPS clearly observed that the CC / CH bond content gradually decreased, while the COO-functional group content gradually increased. At the same time, the O1s graph of XPS clearly observed that the COO-functional group content gradually increased with the increase of the number of cycles. The corresponding results show that ozone oxidation depolymerization of SL and NMH can effectively crack CO and CC bonds in lignite, and the product has relatively more carboxyl functional groups.

[0064] SEM characterization was used to observe the morphological characteristics of different lignite samples and the corresponding oxidation residues. Fig.12 As shown in the figure, the surfaces of all lignite samples including SL, NMH, XLT and SDP are relatively smooth, similar to stones. After ozone oxidation, the lignite samples gradually began to precipitate organic matter, the surface became very rough, and more porous structures were formed. For the same type of lignite, taking SL as an example, as the oxidation time increases, the more fully the coal sample is oxidized, the more organic matter is precipitated, and more porous structures are formed on the surface; as the ozone production in the oxidation process increases, the oxidation effect of the coal sample is relatively better; compared with water as a solvent, the oxidation effect is better when acetic acid is used as a solvent, and the pore structure of the oxidized residue surface is richer. The results reveal that acetic acid is more conducive to the precipitation of organic matter.

[0065] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite, characterized in that: The following steps are involved: Weigh lignite, add acetic acid or water, introduce a mixed gas of ozone and oxygen into the system, and stir to react at room temperature; after the reaction is completed, centrifuge and filter the mixture to collect a liquid sample.

2. The method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite according to claim 1, characterized in that: The stirring speed is 300-500 rpm, and the stirring time is 1.5-6 h.

3. The method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite according to claim 1, characterized in that: The lignite is selected from one of Shengli lignite, Naomaohu coal, Xiaolongtan coal, Shendong pulverized coal, Shendong lump coal and Mengdong coal.

4. The method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite according to claim 1, characterized in that: The solid-liquid ratio of the lignite to acetic acid or the lignite to water is 1-4:30 g / mL.

5. The method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite according to claim 1, characterized in that: The ozone is generated by the following steps: high-purity oxygen is introduced into the ozone generator, the flow rate of oxygen is adjusted to 0.5 L / min, and the ozone output is 20-40 m 3 / h, the mixed gas of ozone and oxygen passes through the ozone detector and then directly into the acetic acid or water system.

6. The method for preparing solvent-soluble components by ozone oxidative depolymerization of lignite according to any one of claims 1 to 5, characterized in that: The solid residue obtained by centrifugal filtration is directly added to acetic acid or water for re-oxidative depolymerization.

Citation Information

Patent Citations

  • Method for depolymerizing lignite by using ionic liquid

    CN102134502A

  • Aqueous alkali depolymerization of coal with a quinone

    US4539095A

Cited By

  • Method for preparing humic acid through ultrasonic-enhanced ozone oxidation depolymerization of lignite

    CN119978431A